Case-control studies: Design issues for criminological applications - Goodman, Richard A. (Journal of quantitative criminology, 1988)
The current understanding of the determinants of homicide derives primarily from studies in which data are aggregated for geopolitical units. Case-control studies and other analytic methods are needed to test causal hypotheses regarding the risk of homicide victimization or perpetration for individuals. Strengths and limitations of the case-control method are illustrated by comparing the design with cohort studies. Fundamental issues include the selection and comparability of cases and controls, effects of biases, interpretation of risk estimates, and problems of implementation. Increased use of this method should advance our understanding of homicide and other forms of intentional violence.